1990
DOI: 10.5006/1.3585045
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamic Perspective of Copper Tarnishing in Moist Air—SO2

Abstract: The open-circuit potential (E"p) of alloy 600 in lithiated water at 25 to 200°C is more negative than the RHE potential, which indicates that the alloy exhibits a mixed electrode potential under these conditions. In the 200 to 350°C range, E op is close to the RHE potential.The inner layer of the oxide film formed at 200°C and above is composed of MeO, white its outer layer is probably composed of Me00H or Me(OH) 2 .With increasing temperature, the film thickness increases moderately between 25 and 200°C, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For example, for copper it was not possible to produce a surface layer similar to the naturally formed patina using gaseous pollutantes like SO 2 and NO 2 . [1][2][3][4][5][6][7][8][9] However, the 1930s, Vernon demonstrated that dust particles, especially dust particles consisting of ammonium sulfate, significantly influence the corrosion of copper and lead to higher corrosion rates. [10][11][12][13][14][15][16] The factors that determine the amount of ionic surface contamination relevant for atmospheric corrosion on metal surfaces was later studied by Sinclair et al [17][18][19][20][21][22][23] The extent of ionic deposition on indoor surfaces is influenced by the concentration of dust particles in the outdoor air, the air exchange rate between indoors and outdoors, efficiency of air filtration systems, the velocity of the air, the surface area to volume ratio, the temperature of the surface, the distance between surfaces and source of particles, and the orientation of the surface.…”
mentioning
confidence: 99%
“…For example, for copper it was not possible to produce a surface layer similar to the naturally formed patina using gaseous pollutantes like SO 2 and NO 2 . [1][2][3][4][5][6][7][8][9] However, the 1930s, Vernon demonstrated that dust particles, especially dust particles consisting of ammonium sulfate, significantly influence the corrosion of copper and lead to higher corrosion rates. [10][11][12][13][14][15][16] The factors that determine the amount of ionic surface contamination relevant for atmospheric corrosion on metal surfaces was later studied by Sinclair et al [17][18][19][20][21][22][23] The extent of ionic deposition on indoor surfaces is influenced by the concentration of dust particles in the outdoor air, the air exchange rate between indoors and outdoors, efficiency of air filtration systems, the velocity of the air, the surface area to volume ratio, the temperature of the surface, the distance between surfaces and source of particles, and the orientation of the surface.…”
mentioning
confidence: 99%
“…Grossman [6] has investigated the atmospheric factors which determined the time of wetness of the outdoor structures. A thermodynamic perspective of copper tarnishing by SO 2 in the presence of moisture was reported by Chawla and Payer [7]. Walters [8,9] carried out some exhaustive studies on the laboratory simulation of atmospheric corrosion by SO 2 detailing the apparatus, electrochemical techniques, and example results.…”
Section: Introductionmentioning
confidence: 99%